Integrating Augmented Reality in RME-Based Digital Learning: Impact on Students' Problem-Solving Ability - Sujinal Arifin; Arvin Efriani (Hipotenusa: Journal of Mathematical Society, 2025)
This research investigates the efficacy of combining Augmented Reality (AR) technology with the Realistic Mathematics Education (RME) methodology in developing students' mathematical problem-solving capabilities. The investigation examines how the AR-RME integration functions as a potential educational innovation for boosting learner involvement and conceptual comprehension. This research employs a combined design incorporating numerical and descriptive-analytical frameworks. A cohort of 17 secondary school adolescents engaged in AR-RME-facilitated learning across five instructional sessions. Evaluation of participants' problem-solving proficiency was conducted through comparative pre-intervention and post-intervention assessments based on Polya's four-stage methodology: issue identification, procedural planning, implementation of strategies, and outcomes evaluation. Systematic observations were conducted to evaluate student engagement levels. The results of the observations showed the enthusiasm and active participation of the students during the learning. Statistical analysis using paired t-tests revealed a significant improvement in problem-solving skills (t = 8.742, p < 0.05), with the average score increasing to 74.81%. These findings show that AR-RME effectively improves spatial reasoning and understanding of three-dimensional geometry concepts, especially on cubes and blocks. This study confirms that AR-RME is an innovative approach that enhances problem-solving skills and becomes a more interactive and effective learning alternative to conventional methods.